Mature tertiary lymphoid structure associated CD103+ CD8+ Trm cells determined improved anti-tumor immune in breast cancer - Fang, Qin; Chen, Shuru; Chen, Xiaoyue; Zou, Wei; Chen, Di; Huang, Yukang; Wu, Chucheng (Frontiers in Oncology, 2025)
BackgroundAlthough tertiary lymphoid structures (TLS) play crucial roles in the anti-tumor immune response and are associated with favorable prognoses in many solid tumors, the precise mechanisms by which TLSs enhance anti-tumor immunity remain poorly understood. The current study aimed to explore the relationship between the maturity of tertiary lymphoid structures and their key immune cells in combating breast cancer.Patients and methodsIn this study, we utilized immunofluorescence and H&E staining to detect tumor-resident memory T cells (Trm) and assess the maturity of TLS, analyzing their distribution and proportion in an annotated cohort of 95 breast cancer patients.ResultsThe presence of tumor-associated TLSs was correlated with an improved prognosis in patients with breast cancer. The proportion of CD8+CD103+ resident memory T cells and natural killer (NK) cells within the TLSs was significantly higher than that in areas outside of these structures. Additionally, the proportions of CD103+ CD8+ Trm cells and NK cells were significantly increased with the gradual maturation of TLS. Furthermore, the secretion function of effector molecules by CD8+ CD103+ Trm cells and NK cells within TLSs was significantly enhanced, indicating a strong correlation between the effector function of CD103+ CD8+ Trm and NK cells and the maturity of TLSs.ConclusionOur study identifies potential additional prognostic information for the clinical prognosis of breast cancer patients, underscoring the prognostic significance of immune cells within TLS, with a particular focus on CD103+ CD8+ Trm cells and NK cells.